Comprehensive screening for PRSS1, SPINK1, CFTR, CTRC and CLDN2 gene mutations in Chinese paediatric patients with idiopathic chronic pancreatitis: a cohort study. Issue 9 (2nd September 2013) - Wang, Wei; Sun, Xiao-Tian; Weng, Xiao-Ling; Zhou, Dai-Zhan; Sun, Chang; Xia, Tian; Hu, Liang-Hao; Lai, Xiao-Wei; Ye, Bo; Liu, Mu-Yun; Jiang, Fei; Gao, Jun; et al.
Abstract : Objective: Genetic alterations may contribute to chronic pancreatitis (CP) in Chinese young patients. This study was designed to investigate mutations of cationic trypsinogen ( PRSS1 ), pancreatic secretory trypsin inhibitor or serine protease inhibitor Kazal type 1 ( SPINK1 ), cystic fibrosis transmembrane conductance regulator (CFTR), chymotrypsin C (CTRC) and CLDN2 genes and the copy number variations (CNVs) of PRSS1 and asses associations with the development of idiopathic CP (ICP) in Chinese children. Design: Retrospective. Setting: A single center. Participants: 75 ICP Chinese children (40 boys and 35 girls). Primary and secondary outcome measures: Mutations of PRSS1, SPINK1, CFTR, CTRC and CLDN2 genes and CNVs. Results: 7 patients had heterozygous mutations in PRSS1, that is, N29I (n=1), R122H or R122C (n=6). The CNVs of PRSS1 in five patients had abnormal copies (1 copy (n=4), five copies (n=1)). 43 patients had IVS3+2T>C (rs148954387) (10 homozygous and 33 heterozygous) in SPINK1 . None of the PRSS1 mutation patients carried a SPINK1 mutation. Frequency of PRSS1 and SPINK1 mutations was 9.3% and 57.3%, respectively, with an overall frequency of 66.6% (50/75). In addition, one patient had a novel deletion of CFTR (GCTTCCTA from c.500 to c.508 leading to the shortened polypeptide molecule via a stop codon). Another patient had a novel missense in CLDN2 exon 2 (c.592A>C mutation). Clinically, patients with SPINK1 mutations had a higher rate of pancreatic duct stones, pancreatic pseudocyst and pancreatic calcification than those without SPINK1 mutations (p<0.05). Conclusions: SPINK1 mutations were more commonly associated with Chinese children with ICP. SPINK1 IVS3+2T>C mutation may play an important role in the pathogenesis of Chinese paediatric ICP. However, further study is needed to confirm and to investigate the role of these genes in the development of Chinese ICP.